2016
DOI: 10.1177/0276146715623051
|View full text |Cite
|
Sign up to set email alerts
|

Religion-Related Research in the Journal of Macromarketing, 1981-2014

Abstract: This study provides a review of religion-related research published in the Journal of Macromarketing (JMK) from 1981 to 2014. A systematic review of the journal identifies 19 key articles at the intersection of religion and macromarketing. Both quantitative and qualitative approaches are utilized to review this body of work in terms of frequency, content, methodology, and authorship. Results reveal four categories of religion-related research in JMK: 1) the impact of religion on macromarketing issues, 2) the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 46 publications
4
40
0
Order By: Relevance
“…First, our study contributes to a better understanding of the reciprocal interaction between marketing and religion in the context of emerging religious movements. In their review, Drenten and McManus (2015) suggest that despite Mittelstaedt's (2002) work on how marketing 41 41 influences religion as a key area of interest for religion and marketing research, scholarship in this field is very limited. They also suggest that more research is needed to examine the reciprocal interaction between marketing and religion, and specifically "how marketing erodes, advances, or sustains religious structures and consumers' religious practices" (p. 9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, our study contributes to a better understanding of the reciprocal interaction between marketing and religion in the context of emerging religious movements. In their review, Drenten and McManus (2015) suggest that despite Mittelstaedt's (2002) work on how marketing 41 41 influences religion as a key area of interest for religion and marketing research, scholarship in this field is very limited. They also suggest that more research is needed to examine the reciprocal interaction between marketing and religion, and specifically "how marketing erodes, advances, or sustains religious structures and consumers' religious practices" (p. 9).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies in macromarketing have often investigated how the globalization of markets, brands and products affect local consumers and their religious beliefs (Drenten and McManus 2015; see among others Eckardt and Mahi 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In undertaking this study, the research addresses the lack of quantitative research in this field (Drenten and McManus, ) by unravelling the relationships between consumer religiosity and their attitude towards generic “food,” and “meat” products that have been produced in accordance with religious doctrine. By responding to Mukhtar and Butt's () call, this research aims to discover whether persons of one faith act with indifference, tolerance, or abhorrence towards foods that are designated for persons of another faith.…”
Section: Research Purposementioning
confidence: 99%
“…The literature provides examples of the integration of Catholic narratives and social thoughts (Abela, ) in several research topics: ethical issues in marketing (Arli, ; Klein & Laczniak, ); marketing strategy development (Laczniak & Klein, ; Laczniak, Klein, & Murphy, ); nonprofit advertising (Hopkins, Shanahan, & Raymond, ); entrepreneurship education (Naughton & Cornwall, ; Toledano & Karanda, ); or the influence of religion on sustainability stewardship (Leary, Minton, & Mittelstaedt, ). However, Drenten and McManus (), who made a systematic review of the intersection between marketing and religion between 1981 and 2014, revealed that more research is needed to better understand the relationship between religion and macromarketing. More recently, Kurenlahti and Salonen () claimed for a holistic and multidimensional approach to consumerism from the religious perspective.…”
Section: Introductionmentioning
confidence: 99%